Pendekatan Pakematik untuk Meningkatkan Hasil Belajar IPA Pokok Bahasan Kemagnetan pada Siswa Kelas IX E SMP Negeri 1 Gabus Kabupaten Grobogan: Array - Sri Sadini (Citra Dharma Cindekia, 2023)
This study aims to improve learning outcomes on the subject of magnetism using a practical approach to class IX E students of SMP Negeri 1 Gabus semester II of the 2021/2022 academic year. The research location is at SMP Negeri 1 Gabus. The time of the research was from January 2022 to March 2022. The research subjects were students in class IX E of SMP Negeri 1 Gabus. Data were collected using observation techniques, questionnaires, and multiple choice written tests. The results of student activity and student responses to the use of a systematic approach developed for the better. The percentage of observations in cycle I was 55.2% (enough category) and in cycle II increased 17.00% to 72.2% (good category). Student learning outcomes experienced an increase in the pre-cycle of students who completed learning by 20 or by 64.5%, in cycle I by 23 or by 74.2%, and in cycle II by 28 or by 90.3%. The magnitude of the increase from pre-cycle to cycle I was 9.7% and from cycle I to cycle II was 12.9%. The conclusion from this study is that a practical approach can improve learning outcomes in science on the subject of magnetism in class IX E students of SMP Negeri 1 Gabus, Grobogan Regency.